2021
DOI: 10.3389/fcell.2021.783050
|View full text |Cite
|
Sign up to set email alerts
|

PDE4B Induces Epithelial-to-Mesenchymal Transition in Bladder Cancer Cells and Is Transcriptionally Suppressed by CBX7

Abstract: Urinary bladder cancer (UBC) is a common malignant tumor with high incidence. Advances in the diagnosis and treatment of this disease demand the identification of novel therapeutic targets. Multiple studies demonstrated that PDE4B level was upregulated in malignancies and high PDE4B expression was correlated with poor outcomes. Herein, we identified that PDE4B was a potential therapeutic target in UBC. We confirmed that PDE4B expression was correlated with aggressive clinicopathological characteristics and unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…It has been reported that PDE4B overexpression is associated with promoting the pathogenesis of hematologic malignancies and some solid tumors, such as colon cancer and bladder cancer [ 24 , 25 ]. However, few studies have explored the exact role of PDE4B in GC.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that PDE4B overexpression is associated with promoting the pathogenesis of hematologic malignancies and some solid tumors, such as colon cancer and bladder cancer [ 24 , 25 ]. However, few studies have explored the exact role of PDE4B in GC.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ORL1 also plays a role as a prognostic gene in the prognostic model of head and neck squamous cell carcinoma based on lipid metabolism-related genes ( Gao et al, 2021 ). It has been shown that PDE4B in our prognostic model gene induces epithelial-mesenchymal transition in bladder cancer cells and is transcriptionally repressed by CBX7 ( Huang et al, 2021 ). These results suggest that our prognostic genes play an important role in cancer, demonstrating that our model is of interest.The PCA and t-SNE plots showed that the model differentiated sufficiently between high- and low-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that embryonic development-related genes were prognostic risk factors for BLCA. Invasion and metastasis of BLCA are thought to be associated with EMT [30,31].Tumor cell stemness regulates tumor cell differentiation, proliferation, invasion and migration [4,[32][33][34].Numerous studies showed that cancer stem cells regulate EMT [35][36][37].Embryonic development is often closely related to stem cells and EMT [5,38,39]. Therefore, we established a micro-landscape of embryonic development-related genes for predicting prognostic risk in BLCA patients.…”
Section: Discussionmentioning
confidence: 99%